BRACHYURY directs histone acetylation to target loci during mesoderm development. (15th November 2017) - Beisaw, Arica; Tsaytler, Pavel; Koch, Frederic; Schmitz, Sandra U; Melissari, Maria‐Theodora; Senft, Anna D; Wittler, Lars; Pennimpede, Tracie; Macura, Karol; Herrmann, Bernhard G; Grote, Phillip
Abstract: T‐box transcription factors play essential roles in multiple aspects of vertebrate development. Here, we show that cooperative function of BRACHYURY (T) with histone‐modifying enzymes is essential for mouse embryogenesis. A single point mutation (T Y88A ) results in decreased histone 3 lysine 27 acetylation (H3K27ac) at T target sites, including the T locus, suggesting that T autoregulates the maintenance of its expression and functions by recruiting permissive chromatin modifications to putative enhancers during mesoderm specification. Our data indicate that T mediates H3K27ac recruitment through a physical interaction with p300. In addition, we determine that T plays a prominent role in the specification of hematopoietic and endothelial cell types. Hematopoietic and endothelial gene expression programs are disrupted in T Y88A mutant embryos, leading to a defect in the differentiation of hematopoietic progenitors. We show that this role of T is mediated, at least in part, through activation of a distal Lmo2 enhancer. Synopsis: T‐box family transcription factors have emerged as regulators of histone modifications. Here, BRACHYURY is shown to bind p300 and facilitate H3K27ac at target gene loci, including those important for hematopoietic specification. BRACHYURY (T) binds p300 and and promotes deposition of H3K27ac at the T genomic locus during early mesoderm development. T plays a prominent role in regulating hematopoietic and endothelial gene expression programs, partly through regulation of the −70 enhancer of Lmo2. Abstract : T‐box family transcription factors have emerged as regulators of histone modifications. Here, BRACHYURY is shown to bind p300 and facilitate H3K27ac at target gene loci, including those important for hematopoietic specification.